Comparison between primary repair and augmented repair with gastrocnemius turn-down flap for acute Achilles tendon rupture: a retrospective study with minimum 2-year follow-up - Shuai Yang; Weili Shi; Wenqiang Yan; Yingfang Ao; Qinwei Guo; Yuping Yang (BMC Musculoskeletal Disorders, 2023)
Abstract Background To explore and compare the clinical outcomes in patients undergoing primary repair versus augmented repair with a gastrocnemius turn-down flap for acute Achilles tendon rupture. Methods From 2012 to 2018, the clinical data of 113 patients with acute Achilles tendon rupture who were treated with primary repair or augmented repair with a gastrocnemius turn-down flap by the same surgeon were retrospectively reviewed. The patients’ preoperative and postoperative scores on the visual analog scale (VAS), American Orthopaedic Foot and Ankle Society Ankle⁃Hindfoot (AOFAS) score, the Victorian Institute of Sport Assessment⁃Achilles (VISA-A), the Achilles tendon total rupture score (ATRS), and the Tegner Activity Scale were examined and compared. The postoperative calf circumference was measured. A Biodex isokinetic dynamometer was used to evaluate the plantarflexion strength on both sides. The time to return to life and exercise as well as the strength deficits in both groups were recorded. Finally, the correlation analyses between patient characteristics and treatment details with clinical outcomes were conducted. Results In total, 68 patients were included and completed the follow-up. The 42 and 26 patients who were treated with primary repair and augmented repair were assigned to group A and B, respectively. No serious postoperative complications were reported. No significant between-group differences in any outcomes were observed. It was found that female sex was correlated with poorer VISA-A score (P = 0.009), complete seal of paratenon was correlated with higher AOFAS score (P = 0.031), and short leg cast was correlated with higher ATRS score (P = 0.006). Conclusions Augmented repair with a gastrocnemius turn-down flap provided no advantage over primary repair for the treatment of acute Achilles tendon rupture. After surgical treatment, females tended to had poorer outcomes, while complete seal of paratenon and short leg cast contributed to better results. Level of evidence Cohort study; Level of evidence, 3.